The value of sex hormones and sex hormone-binding globulin in metabolic dysfunction-associated fatty liver disease among boys with obesity - Ying Wang; Shuyi Yang; Suming Zhang; Suming Zhang; Ye Yang; Siqing Li; Siqing Li; Meiyu Zhang; Meiyu Zhang; Xiaona Li; Hua Bai; Peiliang Luo; et al. (Frontiers in Endocrinology)
ObjectiveThis study aims to investigate the relationship between metabolic dysfunction-associated fatty liver disease (MAFLD) and sex hormones and sex hormone-binding globulin (SHBG) in boys with obesity.MethodsRetrospective analysis of metabolic indicators and sex hormone levels in boys with obesity who sought medical attention at the First People’s Hospital of Lianyungang City from January 2020 to December 2023. Based on abdominal ultrasound results, they were categorized into a simple obesity group and MAFLD group, and differences between the two groups were compared. Utilizing logistic regression analysis to explore the risk factors for developing MAFLD, and through the construction of Receiver Operating Characteristic (ROC) curves, conducting a preliminary assessment of the diagnostic value for MAFLD.ResultsA total of 155 male children with obesity were included in the study, mean age of 11.07 ± 1.53 years. Children in the MAFLD group had higher levels of height[(159.49 ± 12.73)cm vs.(155.55 ± 10.50)cm], weight[(82.32 ± 18.75)kg vs.(68.28 ± 15.00)kg], BMI[(32.08 ± 4.49)kg/m2 vs.(27.85 ± 4.21)kg/m2],fasting insulin[33.42(24.07,43.93)uIU/ml vs.23.91(15.72,31.52)uIU/ml],HOMA-IR[7.27(5.26,10.71) vs.4.87(3.27,6.86)],fastingC-peptide[1409.00(1175.00,1668.00)pmol/L vs.1020.00(849.05,1303.00)pmol/L], WBC[(7.85 ± 1.80)×109/L vs.(7.15 ± 1.42)×109/L], HbA1c[5.40(5.30,5.70)% vs.(5.30(5.20,5.60)%],ALT[48.00(27.00,80.00)U/L vs.19.00(15.00,26.50)U/L], and AST[31.00(24.00,60.00)U/L vs.21.00(18.50, 26.00)U/L] compared to the simple obesity group (P<0.05). Children in the MAFLD group had lower levels of HDL[(1.05 ± 0.21)mmol/L vs.(1.16 ± 0.26)mmol/L], testosterone [42.41(30.33,143.28)ng/dl vs.125.41(23.41,221.57)ng/dl], and SHBG[13.20(9.10,17.30)nmol/l vs.19.60(13.50,29.85)nmol/l] compared to the simple obesity group (P<0.05). Logistic regression showed that BMI, testosterone, and SHBG were independent risk factors for MAFLD in boys, and ROC curve analysis indicated their potential value in the early diagnosis of MAFLD.ConclusionBMI, testosterone, and SHBG are independent risk factors for the occurrence of MAFLD in boys with obesity. To control the occurrence of MAFLD, it is essential to address the root cause of the high growth rate of obesity. The roles of testosterone and SHBG in MAFLD merit further research.